P264 Kawasaki disease in three-month-old boy following immunisation with rotavirus vaccine. (6th June 2017) - Erat, Tuğba; Yahşi, Aysun; Kara, Tuğçe Tural; Özdemir, Halil; Tutar, Ercan; Ince, Erdal; Çiftçi, Ergin
Abstract : We report a case of 3-month-old boy who developed Kawasaki disease (KD) after receiving his first dose of rotavirus vaccine. In our patient, fever had been ongoing for the last 12 days and his physical examination revealed bilateral non-exudative conjunctivitis and a left cervical 1.5 × 2 cm lymph node. He had received his first dose of rotavirus vaccine (Rotarix) 13 days ago. On echocardiography, dilatation was seen in the left coronary artery. Atypical KD diagnosis was established on the 13th day. Inflammatory response was received following high dose IVIG and aspirin treatment, but coronary dilatation was developed at the time of diagnosis. This was the first case presented in Turkey with Kawasaki disease developed following rotavirus immunisation. This report emphasises the importance of keeping in mind KD in the cases of prolonged fever after rotavirus vaccination.